Relationship between Knowledge of Periodontal Disease and Gingival Melanin Pigmentation and Smoking Behavior - Widhani, Farisa D. P.; Nosartika, Isniya; Kusuma, Ira A.; Prabowo, Yoghi B. (e-GiGi, 2022)
Abstract: Tobacco use in Indonesia is still relatively high among teenagers-adults or the average of university students. There is a relationship between smoking and periodontal tissue parameters as well as gingival melanin pigmentation. This study aimed to determine the relationship between the knowledge of periodontal disease and gingival melanin pigmentation and smoking behavior among college students. This was an analytical and observational study with a cross-sectional study design. Samples were 108 undergraduates of Diponegoro University batch 2018-2020 who met the inclusion criteria, obtained by using purposive sampling and non-probability sampling techniques. Data were collected by using an online questionnaire through the Google platform regarding the knowledge of periodontal disease and gingival melanin pigmentation on smoking behavior. The data were analyzed by using the Spearman Rank Correlation Test. The results showed that the students’ knowledge about periodontal disease and gingival melanin pigmentation was in a good category, meanwhile students’ smoking behavior was in the moderate smoker category. The Spearman Rank correlation test showed no significant correlation between knowledge of periodontal disease and gingival melanin pigmentation with smoking behavior (p=0.403). In conclusion, there was no significant relationship between the knowledge of periodontal disease and gingival melanin pigmentation and smoking behavior.Keywords: knowledge; behavior; smoking; periodontal disease; gingival melanin pigmentation Abstrak: Penggunaan tembakau di Indonesia masih tergolong tinggi di kalangan usia remaja-dewasa atau rata-rata usia mahasiswa. Terdapat keterkaitan antara merokok dengan parameter jaringan periodontal dan perubahan pigmentasi melanin gingiva. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan penyakit periodontal dan pigmentasi melanin gingiva dengan perilaku merokok mahasiswa. Jenis penelitian ialah observasional analitik dengan desain potong lintang. Sampel penelitian ialah 108 mahasiswa Strata 1 Universitas Diponegoro angkatan 2018-2020 yang memenuhi kriteria inklusi diperoleh dengan teknik sampel purposive sampling dan teknik pengambilan sampel non-probability. Pengambilan data dilakukan dengan menggunakan kuesioner online melalui platform Google form tentang pengetahuan penyakit periodontal dan pigmentasi melanin gingiva terhadap perilaku merokok. Analisis statistik menggunakan uji korelasi Spearman rank dengan menggunakan aplikasi statistik SPSS. Hasil penelitian mendapatkan tingkat pengetahuan penyakit periodontal dan pigmentasi melanin gingiva mahasiswa dalam kategori baik, dan untuk perilaku merokok mahasiswa termasuk dalam kategori perokok sedang. Uji korelasi Spearman rank menunjukkan bahwa tidak terdapat hubungan bermakna antara pengetahuan penyakit periodontal dan pigmentasi melanin gingiva dengan perilaku merokok (p=0,403). Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara pengetahuan penyakit periodontal dan pigmentasi melanin gingiva dengan perilaku merokok pada mahasiswa Strata 1 Universitas Diponegoro.Kata kunci: pengetahuan; perilaku; merokok; penyakit periodontal; pigmentasi melanin gingiva